Manajemen Bank Sentral Dan Aplikasinya Di Indonesia - Az Zahra Nuril Firdaus; Rini Puji Astuti; Tika Puji Susanti; Risa Astutik; Siti Nadila Nur Oktavia (Jurnal Ekonomi dan Bisnis Digital, 2024)
The Central Bank has a vital and strategic role for society and economic development. The most basic thing is the role of the central bank in printing and circulating money. With this role, the central bank has the goal and responsibility to achieve and maintain the stability of the value of the currency in circulation and to support the achievement of this goal, the central bank needs to have central bank independence. Independence is an important factor in achieving the central bank's ultimate goal, namely achieving stability in the value of money. The research method used is a qualitative method with data collection, namely observation. The issues that will be discussed in this article are related to Central Bank Management in managing a country's economy and its relationship with the economy in Indonesia. The parameters used to measure the quality of independence of central bank management can refer to: first, the authority and relationship of the central bank with the government, second, the importance of independence, accountability and transparency of the central bank and third, the organization of Indonesian banks. The conclusion that can be drawn is to reorganize the management and independence of Bank Indonesia because the Indonesian banking institution is an institution that plays an important role in the monetary sector.